Impact of nitrogen supply on leaf water relations and physiological traits in a set of potato (Solanum tuberosum L.) cultivars under drought stress. (21st January 2018) - Meise, P.; Seddig, S.; Uptmoor, R.; Ordon, F.; Schum, A.
Abstract: Improved adaptation of potato to limited water availability is needed for stable yields under drought. The maintenance of the cell water status and protection of cellular components against dehydration are important for drought tolerance, and the N status of plants affects the regulation of various respective metabolic processes. A 2‐year pot trial with 17 potato cultivars was conducted under a rain‐out shelter including two water regimes and two N‐levels to investigate genotypic differences concerning osmotic adjustment (OA) and relevant biochemical traits in relation to nitrogen (N) supply. Drought stress resulted in a rapid decrease in the leaf osmotic potential. The N, protein and proline contents increased under drought, while the N protein/NK jeldahl ratio decreased. Initially, total soluble sugars increased at both N‐levels but dropped back to the control level at high N‐availability under prolonged drought while remaining high in N‐deficient plants. Results indicate that potatoes have only a limited capacity of active OA and that increasing sugar and proline concentrations are rather associated with the protection of cellular components. High N supply promoted the N protein/NK jeldahl ratio at short‐term drought and enhanced proline accumulation. Significant genotypic differences were observed for all investigated traits.